A Ruptured Digital Epidermal Inclusion Cyst: A Sinister Presentation - Iain Bohler; Phillip Fletcher; Amanda Ragg; Andrew Vane (Case Reports in Orthopedics)
Epidermal inclusion cysts are benign cutaneous lesions caused by dermal or subdermal implantation and proliferation of epidermal squamous epithelium as a result of trauma or surgery. They are typically located on the scalp, face, trunk, neck, or back; however they can be found anywhere on the body. Lesions are asymptomatic unless complicated by rupture, malignant transformation to squamous cell carcinoma, or infection at which point they can clinically appear as more sinister pathologies. We present the case of a 45-year-old laborer with a ruptured epidermal inclusion cyst, manifesting clinically and radiographically as a malignancy. Following MRI, definitive surgical management may appear to be a logical progression in management of the patient. This case however is a good example of why meticulously following surgical protocol when evaluating an unknown soft tissue mass is imperative. By following protocol, an alternate diagnosis was made and the patient has since gone on to a make a full recovery without life transforming surgery.